Green synthesis of cerium oxide nanoparticles via Linum usitatissimum seeds extract and assessment of its biological effects - Zahra Foroutan; Zahra Sabouri; Amir Reza Afshari; Asma Mostafapour; Bahareh Farasati Far; Mohammad Jalili‐Nik; Majid Darroudi (Micro & Nano Letters)
Abstract In the current work, CeO2‐NPs were produced via a green chemistry process via Linum usitatissimum seeds extract as the stabilizing agent. The CeO2‐NPs were characterized by the results of analytical techniques such as TGA/DTA, FTIR, UV–vis, XPS, XRD, and FESEM/PSA/EDX. The outcomes of the XRD pattern affirmed the crystalline structure of this product with the suggested size of about 20 nm, while the FESEM/PSA pictures presented spherical morphology. Additionally, the XPS analysis of CeO2‐NPs affirmed the presence of a Ce+3 oxidation state in the sample, as well as Ce+4 as the major valence of cerium oxide. The results of the MTT test on Huh‐7 cancer cells and HFF normal cells displayed the lack of any significant cytotoxicity even at concentrations up to 1000 µg/mL. Therefore, the obtained synthesized CeO2‐NPs through this green method could be suggested as a prospective agent for medical applications due to its non‐toxic effects.